1996
DOI: 10.1046/j.1365-2133.1996.d01-1103.x
|View full text |Cite
|
Sign up to set email alerts
|

Copper vapour laser treatment of cafe-au-lait macules

Abstract: Café-au-lait macules are skin lesions known to resist all kinds of treatment. Green light at a wavelength of 511 nm from a copper vapour laser through a built-in computerized scanner (SCANALL) was employed to treat café-au-lait-macules in 16 patients. The laser was used in continuous mode with a mean energy density of 8.9 J/cm2 (range 7-22 J/cm2). The mean number of treatment sessions was two. The response was good to excellent in 15 cases and poor in one. Transient hyperpigmentation at the periphery and tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 6 publications
0
16
0
2
Order By: Relevance
“…Self-limiting and transient hyperpigmentation at the periphery and temporary nonhomogeneous hypopigmentation at the center of the treated area was observed in some cases [17].…”
Section: Café-au-lait Maculesmentioning
confidence: 98%
See 1 more Smart Citation
“…Self-limiting and transient hyperpigmentation at the periphery and temporary nonhomogeneous hypopigmentation at the center of the treated area was observed in some cases [17].…”
Section: Café-au-lait Maculesmentioning
confidence: 98%
“…Frequency-doubled QS Nd:YAG [15] QSRL [15,16] Copper vapor laser [17] Pulsed dye laser [18,19,20] Nevus spilus QSRL [22] QS Nd:YAG [22] Melasma Er:YAG [24] Pulsed CO 2 + QSAL [25,26] IPL [27] Fraxel ® [28] Becker's nevus Er:YAG [29,30] QS Nd:YAG [29] Congenital melanocytic nevi QSRL [31,32,33] QS Nd:YAG [31] Pulsed CO 2 + QS Nd:YAG [34] Er: Erbium; IPL: Intense pulsed light; Nd:YAG: Neodymium yttrium aluminum garnet; QS: Q-switched; QSAL: Q-switched alexandrite laser; QSRL: Q-switched ruby laser.…”
Section: Lasermentioning
confidence: 99%
“…46 Reports of overall café-au-lait pigment lightening with the Q-switched ruby laser, the Q-switched alexandrite laser, the Q-switched frequency-doubled Nd:YAG laser, and the copper vapor laser have been published, yet comparative studies have not been conclusive. [89][90][91][92][93][94] Owing to the variable response of café-au-lait macules to all lasers, it is difficult to say that one laser is preferable to another and patients should be advised of potential responses to treatment.…”
Section: Café-au-lait Maculesmentioning
confidence: 99%
“…2,3,6,26,27 We can verify that conventional CVL radiation has a useful application in medicine, specifically in dermatology, but research has focused its application to soft tissue and has not expanded to the field of dentistry. [23][24][25]29,31 High-power lasers used in odontological clinics are argon, CO 2 , Nd:YAG, Ho:YAG, and ER:YAG. Authors have shown that the CVL is a possible substitute for the argon laser in the medical field through comparative research.…”
Section: Discussionmentioning
confidence: 99%